2014
DOI: 10.5812/ircmj.18399
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Promoting Intervention on Healthy Lifestyle and Social Support in Elders: A Clinical Trial Study

Abstract: Background:Many of the problems pertaining to old age originate from unhealthy lifestyle and low social support. Overcoming these problems requires precise and proper policy-making and planning.Objectives:The aim of the current research is to investigate the effect of health promoting interventions on healthy lifestyle and social support in elders.Patients and Methods:This study was conducted as a clinical trial lasting for 12 months on 464 elders aged above 60 years who were under the aegis of health homes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 30 publications
7
34
1
2
Order By: Relevance
“…Compared with control groups, the intervention groups demonstrated a small increase in fruit and vegetable intake (0.31 portions, 95% CI=0.17, 0.45); a small reduction in calorie intake (-83.37, 95% CI= -148.54, -18.20) and fat intake (SMD= -0.24, 95% CI= -0.36, -0.12); and a small increase in physical activity (SMD=0.25, 95% CI=0.13, 0.38). However, the findings for physical activity were sensitive to an individual study 38 where the intervention was more effective than in other studies (SMD¼2.94). When this study was removed from the analysis, the effect estimate (SMD¼0.15, 95% CI¼0.09, 0.21) and heterogeneity (I 2 ¼61% vs 93% when considering all studies) were substantially reduced.…”
Section: Evidence Synthesismentioning
confidence: 88%
“…Compared with control groups, the intervention groups demonstrated a small increase in fruit and vegetable intake (0.31 portions, 95% CI=0.17, 0.45); a small reduction in calorie intake (-83.37, 95% CI= -148.54, -18.20) and fat intake (SMD= -0.24, 95% CI= -0.36, -0.12); and a small increase in physical activity (SMD=0.25, 95% CI=0.13, 0.38). However, the findings for physical activity were sensitive to an individual study 38 where the intervention was more effective than in other studies (SMD¼2.94). When this study was removed from the analysis, the effect estimate (SMD¼0.15, 95% CI¼0.09, 0.21) and heterogeneity (I 2 ¼61% vs 93% when considering all studies) were substantially reduced.…”
Section: Evidence Synthesismentioning
confidence: 88%
“…Research has examined the influence of personal determinants of health on participation in and adherence to health-promoting behavior. Behaviors, such as healthy eating and self-care, have been found to be positively affected by motivation to change (Centis et al, 2014), social support (Levesque, Li, & Pahal, 2012), personality (Lunn, Nowson, Worsley, & Torres, 2014), and self-worth and self-esteem (Huberty et al, 2014). Though, motivation and self-efficacy have also been described as important barriers to diabetes care by both patients and providers (Simmons, Lillis, Swan, & Haar, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is also an effective factor in healthy aging and can prevent elder abuse, along with other health promoting behavior and social support. 2 , 17 , 18 Studies have confirmed the importance of self-efficacy as a determinant of health promoting behavior, 19 , 20 while others have confirmed the relationship between social support and health promoting behavior 20 22 and between self-efficacy and social support. 20 , 23 , 24 The overall aim of this study was to design and evaluate the efficacy of an educational intervention for empowerment of the older adults, focusing on self-efficacy, social support, and health promoting behavior, in order to promote healthy aging and prevent elder abuse.…”
Section: Introductionmentioning
confidence: 97%